2020
DOI: 10.1021/acs.inorgchem.0c00106
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Substitution Mechanism of Antitumor Au(I) N-Heterocyclic Carbene Complexes by Cysteine and Selenocysteine

Abstract: We carried out a detailed theoretical study on the mechanism of the carbene ligand substitution by cysteine and selenocysteine residues in an Au(I) bis-N-heterocyclic carbene complex in order to model the initial stages of the mechanism of action of this promising class of antitumor metallodrug. Both neutral and deprotonated capped Cys and Sec species were considered as possible nucleophiles in the ligand exchange reaction on the metal center to model the corresponding protein side chains. Energies and geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 59 publications
2
32
1
Order By: Relevance
“…Although these outcomes might represent a limitation to the employment of non-bonded topological schemes for the description of Pb(II) coordination by sulfur ligands, it should be also taken into account that the binding of thiol at metal centers may often be followed by deprotonation, leading to the corresponding thiolate complex. Several theoretical and experimental evidences have confirmed that a marked decrease of the thiol pKa occurs upon coordination at even soft metal centers such as Au(I) [66][67][68][69], Au(III) [70] and also Pb(II) [23]. Thus, the use of empirical force field implemented with non-bonded potentials describing the Pb(II) coordination at sulfur ligands may still be considered valuable by assuming the thiolate, and not thiol, as the metal-binding form.…”
Section: Discussionmentioning
confidence: 99%
“…Although these outcomes might represent a limitation to the employment of non-bonded topological schemes for the description of Pb(II) coordination by sulfur ligands, it should be also taken into account that the binding of thiol at metal centers may often be followed by deprotonation, leading to the corresponding thiolate complex. Several theoretical and experimental evidences have confirmed that a marked decrease of the thiol pKa occurs upon coordination at even soft metal centers such as Au(I) [66][67][68][69], Au(III) [70] and also Pb(II) [23]. Thus, the use of empirical force field implemented with non-bonded potentials describing the Pb(II) coordination at sulfur ligands may still be considered valuable by assuming the thiolate, and not thiol, as the metal-binding form.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we assessed seven among the routinely employed and recently developed density functionals for their capability to predict the structure and reactivity of Cl-Pt(NH = C(CH 3 )-O) 2 As(OH) 2 , arsenoplatin (AP), in order to point out the adequate level of theory to use in future investigations on its mechanism of action. In particular, we considered the widely used hybrid GGA functional B3LYP [44,45] and its variant including Grimme's empirical dispersion correction B3LYP-D3 [46], the meta-GGA functional originally designed to study transition metal complexes M06-L [47], the Minnesota hybrid meta-GGA functional M06-2X [48], the one-parameter hybrid GGA functional PBE0 [49] and two more recent range-separated hybrid functionals which have been shown to provide good results for transition metal systems CAM-B3LYP [50] and ωB97X [51], which are known to give a good description of geometries and reaction profiles for transition or heavy metal-containing compounds [52][53][54][55][56], including structure and reactivity of transition metal complexes [57,58], and particularly antitumor Pt-based compounds [32,[59][60][61]. We also considered the influence of the use of three basis sets differing in their size and for the number of polarization and diffuse functions.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in accord with the literature, which provides support for the notion that increasing steric hindrance reduces the rate of ligand exchange between cysteine and Au bis-NHCs. 31,32 Further support for this conclusion came from analogous NMR spectral studies involving complex 8; again, no discernible NHC ligand exchange in presence of cysteine was observed over the course of the study (see Fig. S4 †).…”
Section: Covalent Binding Between Hsa and Au(i) Bis-nhcmentioning
confidence: 70%